Capacidades superiores matemáticas en la enseñanza de la Probabilidad - Chaves Esquivel, Edwin (2019)
The Mathematics curriculum of Costa Rica approved in 2012 poses significant challenges to the authorities of the Ministry of Public Education of the country. Teachers have faced complications in designing learning situations consistent with the curricular fundamentals. Here a mathematical problem is exemplified to be developed in classrooms, and the solution articulates different curricular elements. The interaction of the moment and intensity in which each of these elements is described. Among other aspects, a model developed by the Mathematics Education Reform Project in Costa Rica is exemplified, which relates a series of indicators with three levels of complexity, to assess the level of participation of mathematical processes and capacities in solving problems. This example is expected to be illustrative in promoting a better understanding of the implementation of this curriculum and in supporting coherent educational planning.